Disaster risk reduction and emergency management in prison: A scoping study from New Zealand. (8th February 2017) - Le Dé, Loic; Gaillard, JC
Abstract : This research note provides insights on disaster risk reduction (DRR) and emergency management in New Zealand prisons. It draws upon a scoping study that explores the exposure of prisons and identifies vulnerabilities and capacities of prisoners. This study also documents policies and practices for DRR and emergency management. It reveals that increasing awareness at the national level and improved DRR policies and emergency management initiatives may still prove insufficient to deal with increasing exposure and the particular vulnerability of a quickly growing number of inmates. The intrinsic capacities of these inmates also remain untapped. This research note further highlights the critical lack of collaboration between stakeholders of prison management, DRR and emergency management in New Zealand.